Estudos funcionais da rgs-CaM, uma calmodulina envolvida na supressão de silenciamento por RNA - Makiyama, Rodrigo Kazuo [UNESP] (2014)
RNA silencing is a conserved mechanism activated by double-stranded RNA molecules (dsRNA) that is present in eukaryotes. It plays basic roles in the regulation of gene expression and in host resistance to viruses and transposons. It is known that proteins of different origins, viral or endogenous, are able to suppress RNA silencing, but the mechanism of action of most of them are not fully understood. One of these endogenous suppressor is a protein called rgs-CaM (regulator of gene silencing CaM), which is a calmodulin-like protein (CaM) identified in tobacco plants. Calmodulins are proteins that play important roles in calcium signaling in eukaryotic cells and able to regulate the activity of numerous proteins with diverse cellular functions. Recently, however, rgs-CaM was shown to be a protein involved in the plant response to counterattack viral suppressors. Thus the data available in the literature about rgs-CaM function still contradictory. Taking these into consideration, the objective of this work was to functionally characterize the tobacco rgs-CaM. For such, different approaches were used: study of its interaction with the viral HC-Pro protein, the subcellular localization of this interaction, identification of endogenous proteins that interact with rgs-CaM and functional analysis of transgenic tobacco plants overexpressing or silenced for rgs-CaM. Structural analysis of the rgs-CaM expressed in Escherichia and in silico analysis revealed a protein rich in alpha helix, possessing two globular domains connected by a long alpha helix, and three binding sites for calcium. The presence of calcium led to a change in rgs-CaM secondary structure, suggesting that the flux and binding of Ca2+ by rgs-CaM may be a key point for its funtion during virus-plant interaction. The results of in vivo interaction employing BiFC showed no interaction between rgs-CaM and HC-Pro in the tested conditions, suggesting a possible ...